Investigation of the possibility of using the raw materials of the Ural region in the production of thermopolished flat glass - Kungurova Anastasiya; Khazhiakhmetova Regina; Vlasova Svetlana (E3S Web of Conferences, 2024)
The research work is devoted to the comparison of two glasses of the same composition but synthesized on different quartz materials – Tashlinsky deposit sand and Ural quartz «Crystal Mountain»), otherwise the same raw materials are used. The physicochemical properties of the obtained glasses were determined, and it was revealed that when quartz is used in glassmaking, the light transmission indicators increase. Therefore, such glasses can be classified as “especially transparent”.